Dynamics of Tm-Ho energy transfer and deactivation of the F-3(4) low level of thulium in fluorozirconate glasses - da Vila, L. D.; Gomes, L.; Tarelho, LVG; Ribeiro, SJL; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2004)
The mechanism involved in the Tm3+ (F-3(4))-->Ho3+ (I-5(7)) energy transfer and Tm3+ (H-3(4), H-3(6))-->Tm3+ (F-3(4), F-3(4)) cross relaxation as a function of the donor and acceptor concentrations was investigated in Tm-Ho-codoped fluorozirconate glasses. The experimental transfer rates were determined for the Tm-->Ho energy transfer from the best fit of the acceptor luminescence decay using an expression which takes into account the Inokuti-Hirayama model and localized donor-to-acceptor interaction solution. The original acceptor solution derived from the Inokuti-Hirayama model fits well the acceptor luminescence transient only for low-concentrated systems. The results showed that a fast excitation diffusion that occurs in a very short time (t<<gamma(-2)) reduces the mean distance between an excited donor (D-*) and the acceptor (A). A localized donor-to-acceptor interaction takes place, leading to an exponential decay of donors as an average of the microscopic rate equation solution of each D-*-A pair separated by distance R that contributes in addition to the Inokuti-Hirayama solution. The observation that the experimental transfer rates were always much bigger than the one predicted by the diffusion model, in which the energy transfer process is assisted by excitation migration among donors state, reinforces the existence of a fast excitation diffusion among donor ions before the energy transfer to acceptor already observed in Yb:Er:ZBLAN. The fast excitation diffusion effect was observed to dominate both the Tm-->Tm cross relaxation and Tm-->Ho energy transfer ions from H-3(4) and F-3(4) thulium states, respectively. (C) 2004 American Institute of Physics.